The Effectiveness of WEPCET (Web-Based Fast Reader) Media on Speed Reading Skills - Rahmah, Nur Aulia; Ali, Enjang Yusup; Karlina, Dety Amelia (Papanda Publisher, 2025)
Low reading ability and comprehension among Indonesian elementary students represents a critical educational challenge, as evidenced by declining PISA scores from 371 points in 2018 to 359 points in 2022. This study aimed to develop and evaluate the effectiveness of WEPCET (Web-Based Fast Reader), a web-based learning media designed to enhance speed reading skills and reading comprehension among fifth-grade elementary students. A quantitative quasi-experimental design with pretest-posttest control group was employed, involving 62 fifth-grade students divided into experimental (n=31) and control groups (n=31). The experimental group received instruction using WEPCET media, while the control group underwent conventional teaching methods. Data collection instruments included reading comprehension tests (15 multiple-choice items), reading speed measurement sheets, and student response questionnaires. Statistical analyses comprised normality tests, homogeneity tests, independent sample t-tests, and N-Gain analysis. Significant improvements were observed in the experimental group, with reading comprehension scores increasing from 49.83 to 85.00 and reading speed from 115.77 to 139.16 words per minute. Independent sample t-test results showed significant differences between groups (p < 0.05). N-Gain analysis revealed